Occurrence of microplastics in harbour seals (Phoca vitulina) and grey seals (Halichoerus grypus) from German waters - Philipp, Carolin; Unger, Bianca; Siebert, Ursula (Animals, 2022)
The level of knowledge on microplastic exposure in marine mammals is limited by the access to dead and alive individuals. Focusing on the Northeast Atlantic area, some studies already confirmed the microplastic presence in free-ranging marine mammals, such as harbour porpoises or harbour seals inhabiting the North Sea (NS). In contrast, knowledge on the exposure to grey seals and particularly on specimen inhabiting the Baltic Sea (BS) are scarce. This study examined 63 gastrointestinal tracts (GIT) of harbour seals and grey seals originating from German waters (NS and BS) found between 2014 and 2019. Besides the documentation of microplastic findings, this study is dealing with life history and health parameters, attempting to identify correlations with microplastic presence. This study confirmed beside the presence, the egestion of microplastics (>100 µm; MPs) in the examined seals, without correlations in parasite infestations or inflammation responses. 540 suspected MPs were identified in 62 intestinal samples (42% fibres, 58% fragments), and 228 MPs in seven stomachs (28% fibres, 72% fragments). In accordance, first evidence of the retainment of fragments in the GIT were given. However, no significant difference in MP occurrence was indicated for different sex or age groups